2005
DOI: 10.1111/j.1525-1438.2005.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastases from epithelial ovarian cancer

Abstract: Brain metastasis from epithelial ovarian cancer is uncommon. We studied the presentation, treatment, and prognosis of brain metastasis in a single institution. A retrospective review of clinical details kept in the computer database of gynecologic oncology services in a tertiary institution between 1993 and 2003 was done. A Medline search for English publications on brain metastasis from epithelial ovarian cancer was performed from 1966 to 2003. The study period included 605 patients, and 4 (0.66%) patients de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
(55 reference statements)
1
22
1
1
Order By: Relevance
“…(Anupol, 2002;Brown III, 2005;Chen, 2009;Cohen, 2004;Cormio, 1995, 2003b, Cormio, 2011aD'Andrea, 2005;Kastritis, 2006;Kim, 2007;Kumar, 2003;Lee, 2008;Sanderson, 2002;Sehouli, 2010;Tay & Rajesh, 2005). However Kolomainen et al demonstrated in their series that a brain involvement could be seen quite frequently (one third of their patients) also in patients with FIGO stage I.…”
Section: Clinicopathological Characteristics Of the Primary Tumourmentioning
confidence: 96%
See 3 more Smart Citations
“…(Anupol, 2002;Brown III, 2005;Chen, 2009;Cohen, 2004;Cormio, 1995, 2003b, Cormio, 2011aD'Andrea, 2005;Kastritis, 2006;Kim, 2007;Kumar, 2003;Lee, 2008;Sanderson, 2002;Sehouli, 2010;Tay & Rajesh, 2005). However Kolomainen et al demonstrated in their series that a brain involvement could be seen quite frequently (one third of their patients) also in patients with FIGO stage I.…”
Section: Clinicopathological Characteristics Of the Primary Tumourmentioning
confidence: 96%
“…Although older studies suggested that these patients should undergone only palliative management, in the last 15 year's published studies many authors agree that a multi-modal treatment is the modality of choice in selected patients and can achieve a long-term remission and a better quality of life. (Anupol, 2002;Brown III, 2005;Chen, 2009;Cohen, 2004;Cormio, 1995;Cormio, 2003b;Cormio, 2011a;D'Andrea, 2005;Kastritis, 2006;Kim, 2007;Lee, 2008;Sanderson, 2002;Sehouli, 2010;Tay & Rajesh, 2005). An aggressive multimodal approach should be aimed both to cure local and systemic disease and leads to an improvement in duration and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…-уже у 1,3% больных [9]. По данным ряда авторов [9][10][11][12][13][14][15][16][17][18][19][20][21][22], среди метастазов в головном мозге метастазы РЯ составляют от 0,2 до 11,6%. Причиной низкой встречаемости, вероятно, является от-носительно низкая способность серозного РЯ к гемато-генному метастазированию.…”
unclassified